Towards a ‘transverse inter-sectoral debate’? A Case Study of the Rural Partnership Programme (RPP) in Post-Socialist Lithuania - Macken-Walsh, Áine (Eastern European Countryside, 2010)
By providing a forum for collaboration between diverse stakeholders, a main aim of the governance and rural development model is to ignite a representative and transverse inter-sectoral debate in relation to local development issues. This article identifies some of the determinants that arise in the transferability of the governance and rural development model from its conventional operational context of free-market liberal democracy to the post-socialist rural setting of the Ukmerge district in Lithuania, where a Rural Partnership Programme (RPP) was implemented (2003-2005). The analysis focuses specifically on how elements of the post-socialist context and other more case-specific aspects of the RPP’s operation impacted on the inter-sectoral dynamics of the RPP partnership board’s operation. The attitudes of the sectoral representatives towards the RPP as a model for representative and integrated rural development are explored